Evaluation of polymerase chain reaction (PCR) and culture of buffy coat, whole blood pcr in comparison with whole blood culture for detection of bacteremia - Valle, Demetrio Jr., L.
Bacteremia, which can eventually lead to sepsis, has an overall in-patient mortality of 20% and can reach to 90% to those patients with shock and organ failure. Early detection is imperative so that appropriate antibiotic treatment cna be administered thus, increasing the survival rate of patients. Routine blood culture remains the most sensitive method of detecting bacteremia in the clinical microbiology laboratory. However, it requires incubation, subculturing, biochemical and/or immunologic tests to identify the bacterium, which could delay treatment. With the introduction of polymerase chain reaction (PCR), clinical microbiology laboratories have been presented with an essentail tool that can be developed as a rapid detection method for bacteremia. Unlike culture, it does not require growth of an organism, and has proven to be sensitive and has shorter turnaround time. No study has been made on the use of Gram type-specific PCR testing as a rapid detection method for bacteremia. If a PCR-based testing could unfailingly rule out bacteremia in less time than blood culture, it will allow prompt treatment of patients with true infections. Limited studies have also been done on the usage of the buffy coat as an alternative method for culture. Using routine blood culture as the gold standard, three experimental methods, namely: buffy coat culture, whole blood PCR and buffy coat PCR, were evaluated. The sensitivity, specificity, positive and negative predictive values of each of the three methods were determined. In addition, the significance of the patients' total white blood cell counts is appraised in association with the three experimental and the gold standard methods used. Using the Slovin's formula, the sample size was set at 76 patients based on the blood culture statistics. Inclusion criteria were adult patients with clinical signs and symptoms of sepsis as manifested by two or more of the following conditions: temperature, >38˚C or <36˚C; heart rate, >90 beats per min; respiratory rate, >20 breaths per min, or PaCO2, <32 mm Hg; leukocyte count, >12,000 cells per mm3, <4,000 cells per mm3, or >10% immature (band) forms. Samples were taken only from patients without antimicrobial treatment or those within 48 hours of antimicrobial therapy. Statistical analytical methods used were the Kappa coefficient for the evaluation of the three experimental methods, while the Chi-square test was used to determine the association between the WBC or leukocyte count (greater than >12,000 cells per mm3 or less than 12,000 per mm3) and all of the methods. Buffy coat culture, whole blood PCR and buffy coat PCR all conferred elevated sensitivity, specificity, positive and negative predictive values, with P values less than 0.05, establishing their validity as alternative methods for the routine blood culture in detecting bacteremia. In addition, the Chi-square test showed P values less than 0.05, ascertaining that there was a direct correlation of WBC counts greater than 12,000 cells per mm3 to the occurrence of bacteremia as detected by all of the methods.